2009
DOI: 10.1177/0040517508102308
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Laundering on the Thermal and Water Transfer Properties of Mass-produced Laminated Nanofiber Web for Use in Wear

Abstract: Nanofiber web produced via mass production electrospinning has many potential applications due to its large specific area, very small pore size, and high porosity. Despite such potential, the application of nanofiber web has been limited on account of its poor mechanical properties. In our previous study, the mechanical properties of laminated nanofiber web were investigated, and it was found that the mechanical properties of nanofiber web are sufficient for use as cloth in outdoor wear if a laminating process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…This method allows to determine the passage of water vapor through plastic films, which are not more than 32mm of thick [23,30,31,33,34,41].…”
Section: Water Vapor Permeability (Wvt)mentioning
confidence: 99%
“…This method allows to determine the passage of water vapor through plastic films, which are not more than 32mm of thick [23,30,31,33,34,41].…”
Section: Water Vapor Permeability (Wvt)mentioning
confidence: 99%
“…Copyright © 2007, SAGE Publications. f, g: Reprinted with permission from Kimura et al [25]. Copyright © 2010, SAGE Publications) Kang et al first used direct electrospinning of PU onto the substrate fabrics (polyester/nylon blended fabric, which contained stainless steel yarn in weft) to prepare the waterproof-breathable fabric.…”
Section: Breathable and Waterproof Clothingmentioning
confidence: 99%
“…They suggested that the hot-melt laminating method is more suitable for nanofiber web lamination and the maintenance of nanofiber web morphology despite repeated laundering allows the retention of the water and thermal transfer properties of the material (Fig. 14.2f, g) [25,27]. Yoon et al developed the waterproof-breathable materials by fabricating layered fabric systems with varying composite structures.…”
Section: Breathable and Waterproof Clothingmentioning
confidence: 99%
“…Here, hydrophobic hexadecyltrimethoxysilane-functionalized graphene oxide (FG, hydrophobic agent) and low-melting thermoplastic polyurethane (TPU, fiber binders) were introduced into PU/FPU electrospinning solutions. The introduction of the hydrophobic FG sheet structure and the formation of the inter-fiber fusion structure by TPU improved not only the waterproofness but also the mechanical performance of the nanofiber WB fabric, which would be an appropriate candidate in various applications, especially for fabricating of protective garments and self-cleaning materials [26][27][28].…”
Section: Introductionmentioning
confidence: 99%